Off-label use of tacrolimus in children with Henoch-Schönlein purpura nephritis: a pilot study. Issue 8 (13th March 2018) - Zhang, Dong-Feng; Hao, Guo-Xiang; Li, Chun-Zhen; Yang, Yan-Jun; Liu, Fu-Juan; Liu, Ling; Yuan, Xiao-Ying; Li, Rui-Hong; Dong, Lei; Dong, Qian; Jacqz-Aigrain, Evelyne; Zhao, Wei
Abstract : Background: Tacrolimus is used off-label in the treatment of Henoch-Schönlein purpura nephritis (HSPN) in children, with limited evidence-based data. Based on clinical empirical experience and mechanism of action, tacrolimus might be promoted as treatment for childhood HSPN. The objectives of this pilot study were to assess its effectiveness and safety, and to explore the potential impact of CYP3A5 genotype. Methods: Children with HSPN receiving tacrolimus as empirical treatment were included in this prospective, observational study. Effectiveness was classified as complete remission, partial remission or non-response. General safety data analyses during and after study drug exposure included adverse events, reasons for discontinuation, deaths, laboratory data and vital signs. Trough concentration was determined using high-performance liquid chromatography with tandem mass spectrometry. Pharmacogenetic analysis was performed on the CYP3A5 gene. Results: A total of 20 patients with a mean age of 7.5 (SD 2.1) years participated in the whole process of the study. Twelve patients reached complete remission and eight patients reached partial remission at the end of 6-month treatment. No patients discontinued tacrolimus treatment due to adverse events, and no drug-related adverse events were shown to have a causal association with tacrolimus therapy. Dose-adjusted trough concentration was significantly higher in children with CYP3A5*1 allele as compared with patients with CYP3A5*3/*3 genotype (170.7±100.9 vs 79.8±47.4 (ng/mL)/(mg/kg)). Conclusion: This pilot study showed that tacrolimus might be an effective and well-tolerated drug for the treatment of HSPN in children. CYP3A5 polymorphism had a significant impact on tacrolimus concentration.